Theoretical Study of CO Adsorption on Perfect and Defective Gold Surfaces - Yingying Wang; Bing Xu; Wanyi Shen (Adsorption Science & Technology)
The activities of Au(111), Au(100) and Au(110) surfaces, as well as the activity of an Au adatom on Au(111), Au(100) and Au(110) surfaces have been characterized by density functional theory using CO as a probe. The results clearly show that the activity of Au surfaces towards CO adsorption is attributable to the presence of low-coordinated gold atoms to which the molecule binds. The results may enrich the understanding of CO adsorption on Au surfaces.